Effect modification by fatty liver in the association between triglyceride-Glucose index and new-onset hypertension: a large health-examination cohort study - Yuzhan Lin; Lifeng Wu; Shaorong Yan; Ruixue Sun (Frontiers in Endocrinology, 2026)
Background The triglyceride-glucose (TyG) index is a simple surrogate marker of insulin resistance. Whether baseline fatty liver modifies the association between TyG and incident hypertension has not been evaluated in large longitudinal cohorts. Methods This retrospective cohort study included 66,664 adults without hypertension at baseline who underwent routine health examinations and follow-up. The TyG index was calculated from fasting triglyceride and fasting glucose concentrations and analyzed as both a continuous and categorical variable. Baseline fatty liver status was assessed by abdominal ultrasonography. Participants were followed for a median of 2.37 years (interquartile range, 1.69-3.21 years). Multivariable Cox proportional hazards models adjusted for age, sex, marital status, ethnicity, body mass index, lifestyle factors, cholesterol measures, and liver enzymes were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Effect modification by fatty liver status was evaluated using stratified analyses and a TyG-by-fatty liver interaction term. Joint associations of TyG category and fatty liver status with new-onset hypertension were also examined. Results During follow-up, 13,949 (20.9%) participants developed new-onset hypertension. Higher TyG was independently associated with new-onset hypertension as a continuous variable (HR 1.37, 95% CI 1.30-1.45) and in the highest versus lowest quartile (HR 1.61, 95% CI 1.49-1.75). Participants with both high TyG and fatty liver had the highest risk (HR 1.63, 95% CI 1.52-1.76), and fatty liver significantly modified the TyG-hypertension association (P for interaction <0.001). These associations remained materially unchanged in sensitivity analyses with additional adjustment for family history of hypertension, diabetes status, kidney function, and baseline blood pressure. Conclusions Higher baseline TyG and fatty liver were associated with an increased risk of new-onset hypertension. Baseline fatty liver modified the association between TyG and new-onset hypertension. These findings may help inform the interpretation of TyG-related future hypertension risk according to baseline fatty liver status among adults undergoing routine health examinations.